Epidemiology, diagnosis, and clinical management of endometriosis - Dahab, Amal Abdo; Essa, Bashair Mohammed; Alabsi, Mariam Tariq; Alqarni, Lujain Ayed; Ahmed, Latifah Arafah; Almehzaa, Reem Talal; Alhayki, Maryam Isa; Alhudaib, Rahaf Saad; Al Ismael, Fatema Ghaleb; Aljahdali, Yousef Rajeh; Alokili, Sarah Tourki (International Journal Of Community Medicine And Public Health, 2023)
When it comes to talk about endometriosis, this affects around the world, and the occurrence of this has done to around 176 million women worldwide. This misplaced endometrial tissue responds to changes and undergoes cyclic bleeding and inflammation. As a result, it may produce complications, which includes pain, adhesions, fibrosis, and dysfunction in affected organs. Furthermore, there are currently no biomarkers for diagnosis without procedures. For diagnosing endometriosis, there is a gold standard laparoscopy combined with confirmation. The primary goals in treating endometriosis are to alleviate pain symptoms, improve fertility if desired by the individual affected, and prevent disease progression. The selection of treatment options is influenced by factors, including the extent and position of the illness, the patient’s age, and future family plans. Nevertheless, it is essential to acknowledge that there are limitations and risks involved, such as symptoms potentially returning after stopping treatment or complications that may arise from procedures.